Molecular arrangement of lamellar liquid crystalline structure with virgin coconut oil - Laili, C. R. (Chemical Publishing Co., 2017)
The molecular arrangements of lamellar mesophase of a mixed surfactant system with decanol were studied, before and after the addition of virgin coconut oil (VCO) by employing optical microscope and small-angle X-ray scattering (SAXS). The two methods have enjoyed much success in elucidating information on the molecular arrangements of liquid crystals. The mixed surfactant used are dodecyl trimethylammonium bromide (DTAB) and aerosol-OT (AOT) at a weight ratio of 90:10. The results from the optical pattern show that the water/DTAB:AOT (90:10)/decanol systems were able to solubilized only small amount of virgin coconut oil before transforming into other structures. From the small-angle X-ray scattering spectrum, it was found that the virgin coconut oil molecules to be partitioned between the nonpolar methyl group layers of lamellar liquid crystalline structure. This was indicated by the higher d-spacings value upon addition of virgin coconut oil. Finally, the water molecules located between the polar head groups, showed low penetrating tendency into the layered structure of the mixed surfactants system.